(untitled) (Journal of Applied Botany and Food Quality, 2012)
About 10,000 mass propagated clonal progenies of the medicinal plant Tropaeolum majus L. had been cultivated in an experimental field trial to analyze the large scale cultivation of nasturtium-plants for pharmaceutical utilization. The glucotropaeolin contents of the eight Tropaeolum-clones, which had been established and propagated by in vitro-culture techniques, had been monitored and compared with unselected plants from commercial seed mixtures (sm-plants). Whereas the intra-clonal variation of the glucosinolate levels was significantly lower than the variability of the sm-plants, the glucotropaeolin content in the clonal progenies was markedly lower than in both, in the clonal mother plants as well as in the sm-plants. The proposed explanation for this phenomenon is based on the fact that the genetically identical cloned plants reveal only a very narrow phenotypical amplitude, which accordingly resulted in designated glucosinolate levels due to the certain environmental situations. However, under changing conditions, the corresponding glucotropaeolin content might be much lower. In contrast, the sm-plants reveal – due to the strong genetic heterogeneity – a much broader phenotypical amplitude of their physiological characteristics. Consequently, under changing growth conditions various individual plants may accumulate high amounts of glucotropaeolin. These coherences explain both, firstly, the finding that the clonal mother plants revealed very high glucotropaeolin levels under the certain – maybe spatial limited cultivation conditions – whereas their progenies accumulate far less glucosinolates; and secondly, that the average content in the sm-plants is higher than the mean content of the clonal progenies.These data suggest that the much cheaper growing of nasturtium plants from seeds should be favoured over the more sophisticated in vitro-propagation techniques. Anyhow, for industrial farming there is one great advantage for the usage of in vitro generated Tropaeolum plants: the selected, high glucosinolate-nasturtium clones all reveal a compact growth with short tendrils. Therefore, the mechanical harvest of the corresponding clonal progenies, is quite unproblematic in comparison to the difficile harvest of sm-plants, most exhibiting tendrils of several meters.